The semiotic perspectives of peirce and saussure: A brief comparative study - Mohd Yakin, Halina Sendera; Totu, Andreas (Elsevier Ltd., 2014)
The primary purpose of this paper is to make a comparative analysis between two leading scholars’ perspectives on semiotic theory, namely Charles Sanders Peirce and Ferdinand de Saussure.In addition, it is also aimed at discussing the linkage between communication and semiotic which can be grasped as a signification of symbol or simply as a study of sign in societal life. Apart from the communication field itself, the theory is commonly used as a reference in various fields such as philosophy, linguistic, arts and literature, archeology, architecture, mathematics and so on.The data has been attained by using content analysis technique of various studies on semiotic and related subject.This article is expected to generate positive contribution in underlining the significance of semiotic theory, not only towards the enhancement of the semiotic epistemology but also to other researchers and academicians in related fields or specific areas.